Serological diagnosis of pneumocystosis: production of a synthetic recombinant antigen for immunodetection of Pneumocystis jirovecii - Tomás, A. L. (Sci Rep, 2016)
Diagnosis of Pneumocystis pneumonia (PcP) relies on the detection of P. jirovecii in respiratory specimens obtained by invasive techniques. Thus, the development of a serological test is urgently needed as it will allow the diagnosis of PcP using blood, an inexpensive and non-invasive specimen. This study aims to combine the production of a multi-epitope synthetic recombinant antigen (RSA) and an ELISA test for detection of anti-P. jirovecii antibodies, in order to develop a new approach for PcP diagnosis. The RSA was selected and designed based on the study of the immunogenicity of the carboxyl-terminal domain of the major surface glycoprotein. This antigen was purified and used as an antigenic tool in an ELISA technique for detection of Ig, IgG and IgM antibodies anti-P. jirovecii (patent-pending no. PT109078). Serum specimens from 88 patients previously categorized in distinct clinical subgroups and 17 blood donors, were analysed. The IgM anti-P. jirovecii levels were statistically increased in patients with PcP (p = 0.001) and the ELISA IgM anti-P. jirovecii test presented a sensitivity of 100% and a specificity of 80.8%, when associated with the clinical diagnosis criteria. This innovative approach, provides good insights about what can be done in the future serum testing for PcP diagnosis.